A Meta-Analysis of the Antecedents of Career Commitment. (August 2021) - Zhu, Dan; Kim, Peter Beomcheol; Milne, Simon; Park, In-Jo
Career commitment refers to one's emotional attachment to one's career rather than to one's current working organization. While career commitment has been studied for decades as an important construct in applied psychology research, robust conclusions about its antecedents have not been drawn by empirical research. To address this issue, this research presents the results of a meta-analytic review of the antecedents of career commitment based on data from 156 individual studies (N = 58, 651) conducted between 1980 and 2019. A total of 52 latent antecedents were captured and categorized into five different groups, and the strength, direction and heterogeneity of the relations between career commitment and its antecedents were meta-analytically investigated. Our findings revealed that while individual attributes (e.g. age) alone were weak predictors of career commitment, psychological (e.g. job satisfaction) and organizational factors (e.g. organizational career growth) exhibited medium effect sizes. In addition, among job-related factors, autonomy demonstrated a relatively strong influence on career commitment. The implications are elucidated for researchers and practitioners in the light of these key findings.